FEASIBILITY ANALYSIS OF REINSURANCE WEBSITE USING THE HEURISTIC EVALUATION METHOD - Adam Rachmat; Rifiana Arief (STMIK Royal, 2023)
Abstract: PT. Energi Mandiri Internasional was established on November 22, 2011 as a reinsurance broker consultant and risk management consultancy to ensure the financial stability of reinsurance service users. The company's website; energyre-int.com as a place to self advertise the company with an electronic mail feature to answer questions from potential clients. Heuristic evaluation method was used to test the feasibility of the user interface and analyze the appearance of the interface from the energyre-int.com website. This test was conducted using questionnaires with 34 respondents of reinsurance consulting services users. The results obtained from testing on the Severity rating scale and using the Eight Golden Rules are recommendations for improvement on aspects that have a value of 1 which means that there are errors but can be ignored; Help and documentation with a value of 0.99, the Error Prevention aspect with a value of 0.98, and the Match between system and the real world aspect with a value of 0.91. Keywords: Heuristic Evaluation; Feasibility Analysis; Reinsurance; User interface; Recommendation. Abstrak: PT. Energi Mandiri Internasional didirikan pada 22 November 2011 sebagai pialang dan konsultan reasuransi dan konsultasi manajemen risiko untuk memastikan stabilitas keuangan dari pengguna jasa reasuransi. Website perusahaan tersebut; energyre-int.com sebagai wadah untuk mengiklankan perusahaan dengan fitur surat elektronik untuk menjawab pertanyaan-pertanyaan calon klien. Heuristic evaluation merupakan metode yang digunakan untuk menguji kelayakan user interface dan menganalisis tampilan antar muka dari website energyre-int.com. Pengujian ini dilakukan menggunakan kuesioner dengan 34 responden pengguna jasa konsultasi reasuransi. Hasil yang didapat dari pengujian dalam skala Severity rating dan menggunakan aturan Eight Golden Rules adalah rekomendasi perbaikan pada aspek yang memiliki nilai 1 artinya ada kesalahan tapi bisa diabaikan; Help and documentation dengan nilai 0,99, aspek Error Prevention dengan nilai 0,98, dan aspek Match between system and the real world dengan nilai 0,91. Kata kunci: Evaluasi Heuristik; Analisis Kelayakan; Reasuransi; Antarmuka Pengguna; Rekomendasi.